2022
DOI: 10.5194/angeo-40-519-2022
|View full text |Cite
|
Sign up to set email alerts
|

Arecibo measurements of D-region electron densities during sunset and sunrise: implications for atmospheric composition

Abstract: Abstract. Earth's lower ionosphere is the region where terrestrial weather and space weather come together. Here, between 60 and 100 km altitude, solar radiation governs the diurnal cycle of the ionized species. This altitude range is also the place where nanometre-sized dust particles, recondensed from ablated meteoric material, exist and interact with free electrons and ions of the ionosphere. This study reports electron density measurements from the Arecibo incoherent-scatter radar being performed during su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…Daytime, nighttime, and day-night terminator conditions are presented. Compared to other studies, Baumann et al (2022) observe lower electron densities during sunrise compared to sunset, while the model presented here shows the opposite phenomenon. However, they do note that the difference is not strongly present at 80 km, and they make no mention of any altitudes below 70 km.…”
Section: Discussioncontrasting
confidence: 99%
“…Daytime, nighttime, and day-night terminator conditions are presented. Compared to other studies, Baumann et al (2022) observe lower electron densities during sunrise compared to sunset, while the model presented here shows the opposite phenomenon. However, they do note that the difference is not strongly present at 80 km, and they make no mention of any altitudes below 70 km.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to that, it also shows an asymmetry behavior that the solar variations could not explain. For example, recently Baumann et al (2022) reported the electron density is higher during the sunset than the sunrise. The postulate that the change in the recombination rates is a plausible reason for this observed asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous observation of the D region is very challenging because of the low electron abundance. There are very few direct observational techniques such as sounding rockets (Mechtly, 1974), incoherent scatter radar (Chau and Woodman, 2005;Baumann et al, 2022), very low frequency (VLF) methods (Worthington and Cohen, 2021), and partialreflection radars or medium-frequency (MF) radars (Belrose, 1970;Igarashi et al, 2000;Singer et al, 2008) that are effectively used to measure the D-region electron density (see. e.g., Friedrich and Rapp, 2009, for a review).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, D-region electron density also shows an asymmetrical behavior that can not be explained by the solar variation. For example, recently Baumann et al (2022) reported the electron density is higher during sunset than sunrise. They postulate that the change in the recombination rates is a plausible reason for this observed asymmetry.…”
Section: Introductionmentioning
confidence: 99%